Analisis manufacturing cycle effectiveness (mce) dalam mengurangi non value added activities - Putri, Noviana; Utary, Anis Rachma; Nadir, Maryam (JURNAL MANAJEMEN, 2016)
The purpose of this research is to know the effectiveness of the activities of production process in reducing Non Value Added Activities to Palm Oil Mill PT. Waru Kaltim Plantation in produce Crude Palm Oil (CPO) and Palm Kernel (PK), where the activities of production process consist of Non Value Added Activities and Value Added Activites the review of the Cycle Time and Tandan Buah Segar (TBS) process to Palm Oil Mill.The analysis tools used in this research is Manufacturing Cycle Effectiveness (MCE), that is analyze the effectiveness of production process to reducing or eliminating Non Value Added Activities and do improvement Value Added Activities by using analysis of activity. Analysis of activity in the manufacturing is the Cycle Time, consist of: processing time, inspetion time, moving time, and waiting time/storage time.The results show that the activities of Palm Oil Mill PT. Waru Kaltim Plantation in producing Crude Palm Oil (CPO) and Palm Kernel (PK) are still not ideal. It is shown by the Manufacturing Cycle Effectiveness (MCE) to Crude Palm Oil (CPO) and Palm Kernel (PK) value for the 2014 is 92% and value for the 2015 is 89%. The Manufacturing Cycle Effectiveness (MCE) percentage can be used by the management of Palm Oil Mill PT. Waru Kaltim Plantation for making a plan of reducing and eleminating Non Value Added Activities and doing improvements toward value added activities.Keyword: Manufacturing Cycle Effectiveness, Non Value Added Actiivties, and Value Added Activities.